2021
DOI: 10.1111/aos.15044
|View full text |Cite
|
Sign up to set email alerts
|

Combined biomechanical and tomographic keratoconus staging: Adding a biomechanical parameter to the ABCD keratoconus staging system

Abstract: Purpose: This retrospective cross-sectional study evaluated the potential of an additional biomechanical parameter 'E' as an addition to the tomographic ABCD ectasia/keratoconus (KC) staging. Methods:The Corvis Biomechanical Factor (CBiF) represents the modified linear term of the Corvis Biomechanical Index (CBI) developed based on 448 KC corneas from the Homburg Keratoconus Center (HKC). The CBiF range was divided into five stages (E0 to E4) to create a grading system according to the ABCD stages. Stage E0 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 30 publications
(91 reference statements)
0
42
0
1
Order By: Relevance
“…Several contemporary studies have also investigated the genomic, transcriptomic or proteomic alterations in keratoconus samples 6,17,18 , though stroma degradation were spotted, more multifaceted and precise signals in cell type-specific manners were diluted because of the limitation of bulkinput methods. In addition, previous studies demonstrated that keratoconus is often accompanied by altered biomechanical properties of the cornea, which can be an indicator of healthy and keratoconus eyes [19][20][21][22][23] . Multivariate analysis of risk factors for keratoconus determined that eye rubbing was the most significant predictor for the progression of keratoconus 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Several contemporary studies have also investigated the genomic, transcriptomic or proteomic alterations in keratoconus samples 6,17,18 , though stroma degradation were spotted, more multifaceted and precise signals in cell type-specific manners were diluted because of the limitation of bulkinput methods. In addition, previous studies demonstrated that keratoconus is often accompanied by altered biomechanical properties of the cornea, which can be an indicator of healthy and keratoconus eyes [19][20][21][22][23] . Multivariate analysis of risk factors for keratoconus determined that eye rubbing was the most significant predictor for the progression of keratoconus 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…An interval spacing of 0.58 was defined for CBiF gates of each E-stage. 37 Lower CBiF values indicated higher E-stages. 37 Biomechanically corrected IOP was calculated from finite element simulations that were least affected by corneal properties.…”
Section: Methodsmentioning
confidence: 99%
“… 34 , 36 E-stage was defined by classifying CBiF into five stages (E0–E4) to rank the severity of corneal destablilization. 37 CBiF values ≥5.94 were designated as stage E0. An interval spacing of 0.58 was defined for CBiF gates of each E-stage.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to corneal curvature or thickness change due to the disease, the corneal stiffness and elasticity is already altered. Therefore, the measurement of biomechanical properties is crucial for the detection of subclinical cases, staging and differential diagnosis [40][41][42][43][44]. Most of the aforementioned parameters indicated that the biomechanical properties of normal and keratoconic eyes were significantly different [43][44][45].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Therefore, the measurement of biomechanical properties is crucial for the detection of subclinical cases, staging and differential diagnosis [40][41][42][43][44]. Most of the aforementioned parameters indicated that the biomechanical properties of normal and keratoconic eyes were significantly different [43][44][45]. Consequently, there is the assumption of a significantly smaller deformation of the central cornea in PMD corneas than in healthy corneas [46].…”
Section: Accepted Manuscriptmentioning
confidence: 99%